PENGARUH LITERASI KEUANGAN TERHADAP MINAT MENABUNG MAHASISWA FKIP UNIVERSITAS KLABAT - Seroy, Jesica Andriani; Aseng, Andrew Christian; Lakat, Junior Semuel; Lasut, Elizabeth Meiske Maythy (Nusantara Hasana Journal, 2025)
Students as young people need to be taught about the importance of saving to learn how to manage personal finances well. Meanwhile, financial literacy is a person's financial understanding that can be used to make the right financial decisions, one of which is saving. For this reason, this study aims to test the effect of financial literacy on students' saving intention. This study uses a quantitative descriptive method as a research method. The data collection process uses an adapted questionnaire. Using convenience sampling techniques, the number of respondents obtained in the main study was 115 FKIP UNKLAB students who filled out the questionnaires that were distributed. The data obtained were then analyzed using mean scores and simple linear regression with the results of the study showing that (1) financial literacy is in the high category, (2) students' interest in saving is in the high category, and (3) there is a significant positive effect of financial literacy on students' interest in saving. These results indicate that the higher the level of students' financial understanding, the higher their interest in saving. There are several recommendations given to related parties in relation to this research topic.